Population Structure of Prunus africana Tree Species in of South Western Ethiopia - Nigatu, Marshet; Mulatu, Yigardu (Annals of Arid Zone, 2025)
Understanding the reproduction and recruitment potential of tree species is very important for establishing in-situ seed production area. The main objective of this study was, to assess the population structure and regeneration status of Prunus africana tree species in three sampled natural forests such as Yayu, Bonga, and Masha, South western Ethiopia for establishing seed production area. The systematic sampling method was used to collect the data. Ten transects line running parallel to each other’s at 100m interval were laid out along the gradient and plots 400 m2 (size: 20 m x 20 m each) were laid at 50 m interval along each transect line. A total of 90 plots were used for data collection. For natural regeneration data collection sub sample plots 25 m2 (size: 5 m × 5m) were established at the center and at four corners of each of the main plots. From each plot, total height and DBH of the target tree species were measured using a clinometer and diameter tape respectively. The results of the distribution of the population structure of P. africana showed broken J-shape and irregular patterns across the forests. The regeneration status of P. africana is “good” in Bonga and Masha and “fair” in Yayu sampled natural forest. The population structure of P. africana tree species vary across the study sites. The variation in population structure among the sites highlights the importance of site-specific parameters in selecting seed provenances for conservation and sustainable utilization.